2021
DOI: 10.3390/cancers13236142
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Rewiring Is Essential for AML Cell Survival to Overcome Autophagy Inhibition by Loss of ATG3

Abstract: Autophagy is an important survival mechanism that allows recycling of nutrients and removal of damaged organelles and has been shown to contribute to the proliferation of acute myeloid leukemia (AML) cells. However, little is known about the mechanism by which autophagy- dependent AML cells can overcome dysfunctional autophagy. In our study we identified autophagy related protein 3 (ATG3) as a crucial autophagy gene for AML cell proliferation by conducting a CRISPR/Cas9 dropout screen with a library targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(130 citation statements)
references
References 79 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…Mitochondrial respiration was measured by the oxygen consumption rate (OCR) using the XF Cell Mito Stress Test Kit (Agilent Technologies, 103015–100) on a 96-well Seahorse Bioscience Extracellular Flux Analyzer XF96 (Agilent Technologies) as described previously [ 66 ]. Murine or human cells (5 × 10 5 or 2 × 10 5 , respectively) were seeded in the stress assay medium as described by the manufacturer in XF96 Polystyrene Cell Culture Microplate for 1 h at 37°C without CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial respiration was measured by the oxygen consumption rate (OCR) using the XF Cell Mito Stress Test Kit (Agilent Technologies, 103015–100) on a 96-well Seahorse Bioscience Extracellular Flux Analyzer XF96 (Agilent Technologies) as described previously [ 66 ]. Murine or human cells (5 × 10 5 or 2 × 10 5 , respectively) were seeded in the stress assay medium as described by the manufacturer in XF96 Polystyrene Cell Culture Microplate for 1 h at 37°C without CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In turn, inhibition of autophagy reduced B-ALL cell survival and proliferation 17 . Evidences have found the high expression of ATG3 in various cancers, containing colon cancer 36 , hepatocellular carcinoma 37 , and acute myeloid leukemia 38 , which promoted the development of cancers through accelerating autophagy. Whereas the expression and function of ATG3 in B-ALL id rarely explored.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Baker et al reported that shRNA-mediated ATG3 deletion impaired the autophagy function of AML cells, leading to the upregulation of glycolysis, lactate production, and mitochondrial metabolism in AML cells. Furthermore, the deletion of ATG3 sensitized AML cells to the inhibition of oxidative phosphorylation (OXPHOS), highlighting the metabolic vulnerabilities that leukemia cells acquire from autophagy inhibition [ 54 ].…”
Section: Interplay Between Autophagy and Glycolysis In Aml Cellsmentioning
confidence: 99%